Intestinal intussusception secondary to polyposis in Peutz-Jeghers syndrome - Vidal-Santiago, Daniela; Ramírez-Pérez, José Emilio; Domínguez-León, Cristina Guadalupe; Trinidad-Rodríguez, Williams (International Surgery Journal, 2024)
Peutz-Jeghers syndrome (PJS) is an autosomal dominant syndrome characterized by multiple hamartomatous polyps in the gastrointestinal tract, mucocutaneous pigmentation. We present a case of intestinal intussusception secondary to these polyps.